The Language of Images and the Development of Critical Attitudes in the Classroom: A Didactic Proposal for the Reading of Visual Signs - Barragán Gómez, Rafael Alberto; Gómez Moreno, Wilson (Íkala, Revista de Lenguaje y Cultura, 2012)
As a part of the project "Didactic of the Image", sponsored by Vicerrectoría de Investigaciones y Extensión de la Universidad Industrial de Santander (code 5229), the need for an interpretative study of the relationship between the imaginary and the teaching performance of educators concerning the visual image (or to be exact, concerning the visual signs) has been proposed. Based on the findings derived from this ethnographic work, we aspire to lay the foundations of a specific didactic method which can address this type of signification systems, not only as instruments that facilitate the apprehension of abstract notions by the students, but also as teaching and learning objects whose understanding implies complex thought processes. For this reason, this article proposes, firstly, a theoretical basis which supports the complex cognitive operations involved in the reading of any image; secondly, it attempts to corroborate the above thesis ascribing an argumentative nature to a kind of image–specifically to the political cartoon, considered text and discourse by virtue of its tendency to use sophisticated rhetorical operations inherent to the visual signs–all with the aim to argue that reading images is a process that also promotes critical thought among students in the same way that written texts do.